Control for delayed bilateral teleoperation of a quadrotor. (November 2017) - Slawiñski, E.; Santiago, D.; Mut, V.
Abstract: This paper proposes a cascade control scheme for delayed bilateral teleoperation of a quadcopter. The strategy transforms a 6D real quadcopter to an easy-to-teleoperate 3D virtual quadcopter. The scheme is formed by a P+d plus PID controller for each dof. The analysis based on Lyapunov theory gets as result the way to set the control parameters depending on the magnitude of the asymmetric time delays (forward and backward delays). This technic aims to reach stability, simplicity and good performance in practice. Besides, experimental tests about delayed bilateral teleoperation of a quadcopter including the proposed control scheme are shown in order to evaluate the system performance. Abstract : Highlights: A control scheme for delayed bilateral teleoperation of a quadcopter is proposed. The strategy combines P+d and PID controllers, where the PID-like schemes set is applied to the real quadcopter on an internal loop while three pairs of P+d like-controllers are used in an external bilateral loop to drive an easy-to-teleoperate virtual quadcopter. The whole control scheme can be applied using the current open source autopilots of commercial quadcopters and a common 3D force feedback hand-controller. From the theoretical analysis performed for the delayed nonlinear varying-time teleoperation system, guidelines to calibrate the control system are proposed in order to get stability as well as a performance satisfactory in practice for a significant delay range.